Nuclear transfer in ruminants - Lee, Joon-Hee; Maalouf, Walid E. (Springer, 2014)
Ruminants were the first mammalian species to be cloned successfully by nuclear transplantation. Those experiments were designed to multiply high merit animals (Willadsen, Nature 320(6057):63–65, 1986; Prather et al., Biol Reprod 37(4):859–866, 1987; Wilmut et al., Nature 385(6619):810–813, 1997). Since then, cloning has provided us with a vast amount of knowledge and information on the reprogramming ability of somatic cells to different cell types which became an important basis for stem cell research and human medicine. Nowadays, the goals of most nuclear transfer work vary widely but in most cases the micromanipulation procedures remain the same. However, differences between species require different technical considerations. In this chapter, we describe in detail somatic cell nuclear transfer which is the foremost method for cloning ruminants with specific reference to sheep and cattle.